Mitigating Inequities and Saving Lives with ICU Triage during the COVID-19 Pandemic - White, Douglas B; Lo, Bernard (American journal of respiratory and critical care medicine, 2021)
The burdens of the coronavirus disease (COVID-19) pandemic have fallen disproportionately on disadvantaged groups, including the poor and Black, Latinx, and Indigenous communities. There is substantial concern that the use of existing ICU triage protocols to allocate scarce ventilators and critical care resources-most of which are designed to save as many lives as possible-may compound these inequities. As governments and health systems revisit their triage guidelines in the context of impending resource shortages, scholars have advocated a range of alternative allocation strategies, including the use of a random lottery to give all patients in need an equal chance of ICU treatment. However, both the save-the-most-lives approach and random allocation are seriously flawed. In this Perspective, we argue that ICU triage policies should simultaneously promote population health outcomes and mitigate health inequities. These ethical goals are sometimes in conflict, which will require balancing the goals of maximizing the number of lives saved and distributing health benefits equitably across society. We recommend three strategies to mitigate health inequities during ICU triage: introducing a correction factor into patients' triage scores to reduce the impact of baseline structural inequities; giving heightened priority to individuals in essential, high-risk occupations; and rejecting use of longer-term life expectancy and categorical exclusions as allocation criteria. We present a practical triage framework that incorporates these strategies and attends to the twin public health goals of promoting population health and social justice.